Pencil-beam scanning proton therapy for anal cancer: a dosimetric comparison with intensity-modulated radiotherapy. (September 2015) - Ojerholm, Eric; Kirk, Maura L.; Thompson, Reid F.; Zhai, Huifang; Metz, James M.; Both, Stefan; Ben-Josef, Edgar; Plastaras, John P.
Abstract Background. Concurrent chemoradiotherapy cures most patients with anal squamous cell carcinoma at the cost of significant treatment-related toxicities. Intensity-modulated radiotherapy (IMRT) reduces side effects compared to older techniques, but whether proton beam therapy (PBT) offers additional advantages is unclear. Material and methods. Eight patients treated with PBT for anal cancer were chosen for this study. We conducted detailed plan comparisons between pencil-beam scanning PBT via two posterior oblique fields and seven-field IMRT. Cumulative dose-volume histograms were analyzed by Wilcoxon signed-rank test, and plan delivery robustness was assessed via verification computed tomography (CT) scans obtained during treatment. Results. Compared to IMRT, PBT reduced low dose radiation (≤ 30 Gy) to the small bowel, total pelvic bone marrow, external genitalia, femoral heads, and bladder (all p < 0.05) without compromising target coverage. For PBT versus IMRT, mean small bowel volume receiving ≥ 15 Gy (V15) was 81 versus 151 cm3, mean external genitalia V20 was 14 versus 40%, and mean total pelvic bone marrow V15 was 66 versus 83% (all p = 0.008). The lumbosacral bone marrow dose was higher with PBT due to beam geometry. PBT was delivered with ≤ 1.3% interfraction deviation in the dose received by 98% of the clinical target volumes. Conclusion. Pencil-beam scanning PBT is clinically feasible and can be robustly delivered for anal cancer patients. Compared with IMRT, PBT reduces low dose radiation to important organs at risk in this population. While the clinical benefit of these differences remains to be shown, existing data suggest that limiting low dose to the small bowel and pelvic bone marrow may reduce treatment toxicity.